Uncertainty measurement with the kinematic telescopic bar during industrial robot inaccuracy tests - Józwik, Jerzy; Jacniacka, Elżbieta; Ostrowski, Dawid (ITM web of conferences, 2017)
The subject of this article is the assessment of measurement uncertainty with the kinematic telescopic bar QC20-W in the accuracy test of MOTOMAN HP20 industrial robot. The measurements were performed to determine the statistical uncertainty of error measurement using the system applied. Analysed in tests was the robot’s ability to recreate a circular outline through standard, complex and extended measurement of uncertainty measurement. The obtained results were served to perform rapid evaluation of robot inaccuracy. These uncertainties were based on the information included in the device calibration certificate (estimated with method B) but also on the basis of measurements and statistical data (estimated with method A). These components of the uncertainty budget take relatively small values (uc=0.818÷4.130; U=1.636÷8.260 for k=2, which proves that a properly selected method was applied to the research task. The method of research and calculation precisely identified key uncertainties allowing for an objective assessment of the industrial robot errors carried out with Renishaw the kinematic telescopic bar.